Impact of corporate governance on financial performance: The mediating role of corporate social responsibility - Aoudane, Meryem; Hilali, Majdouline; Mehdi, Sanae (Edelweiss Applied Science and Technology, 2025)
This study aims to explore the relationships between corporate governance (CG), financial performance (FP), and corporate social responsibility (CSR) in listed firms in Morocco, an emerging economy characterized by dynamic economic growth, constantly developing governance mechanisms, and increasing concern regarding ethical behavior in business. Analyzing the data of 68 firms listed in the Casablanca Stock Exchange and using structural equation model (SEM) analysis to test four hypotheses, the analysis confirms a positive link between CG and CSR, with good governance facilitating ethical and responsible behavior in business. CG, in its direct effect, was found to have a significant contribution to financial performance, with good governance structures leading to financial success. CSR, in its effect, was found to have a positive contribution to financial performance, with financial returns for responsible behavior in business. CSR, in its function, plays a mediating role in CG and its effect on financial performance, with governance having not only a direct contribution but also an indirect contribution through CSR behavior to financial performance.